Use of Queatiapine in Treatment of Unremitting Anxiety: A Case Report of Schizophrenia Prodrome - Othman, Zahiruddin; Jaapar, Sharifah Zubaidiah Syed; Husain, Maruzairi; Yasin, Mohd Azhar Mohd (Japan International Cultural Exchange Foundation, 2016)
Objective: A 21-year-old man who presented with a 17-month history of unremitting anxiety associated with panic attacks was studied. Result: The anxiety with panic attacks did not abate with escitalopram 15 mg nocte and alprazolam 0.5 mg tds. At month 3, the patient reported low mood and unexplained sexual arousal in addition to the unremitting anxiety symptoms. His condition fairly improved with addition of quetiapine. At month 17, transition to psychotic disorder occurred when the patient experienced hallucinations for the first time. Quetiapine was increased to 500 mg nocte and the anxiety symptoms improved tremendously before he relapsed 6 months later due to poor compliance. Conclusion: Unremitting anxiety with depression can be a dominant feature during the schizophrenia prodrome. Atypical antipsychotic quetiapine is an interesting treatment option due to its status as approved adjunctive treatment for major depressive disorder and promising efficacy for generalized anxiety disorder.